PENGARUH VARIASI KONSENTRASI BAHAN PENGIKAT PVP (POLYVIYL PYRROLIDONE) TERHADAP MUTU FISIK TABLET KUNYIT (Curcuma domestica Val.) KOMBINASI BROTOWALI (Tinospora crispa L.) (Jurnal Farmasi IKIFA, 2021)
Diabetes mellitus (DM) is one of many chronical disease and Indonesia is being 6st position in world rank. Turmeric (Curcuma domesticaVal.) contain 75% curcumin, and Brotowali (Tinospora crispa) contain of Terpenoid which has compound as antidote for Diabetes. This research intended to formulate Turmeric tablet by using wet granulation method and evaluation the physically quality of tablet. Method of the research that will be used is experimental research. This research is consist of extract making, chemical compounds identification, Tumeric tablet making which combine of Brotowali extract with variation concentrate of binding agent (2,5% and 5%), and physical quality test. Extract is made by Maserasi method and ethanol solvent 70%. Extraction results is formulated to be tablet which contain of Turmeric extract, Brotowali extract, Amilum Manihot, Polivinyl pyrolidone, Magnesiom Stearat, Laktosa, Talkum and Aquadest. Tablet making process consist of granul making by using wet granulation method and physical quality test. Granul physic quality test consist of compression index test, flow speed test, silent angle test, and drying shrinkage. Physical tablet quality test consist of uniformity of weights test, size uniformity test, tablet hardness test, tablet disintegration time test and tablet fragility test. Research result analyzed by using T test with Software SPSS helping.The result of statistic test showing there is influence of variety of amount binder to physical tablet quality. uniformity of weights of second tablet formula shows better result than first tablet formula. The summarize the result of this research, statistic test which is PVP blinder influencing on the uniformity of weight and disintergation time, tablets with pvp concentration of 5% have better uniformity of weight and faster desintregation time compared to tablets with a pvp concentration of 2,5%.